FAKTOR – FAKTOR YANG MEMPENGARUHI HASIL BELAJAR KOMPUTER AKUNTANSI PADA KELAS XI AKUNTANSI SMK MUHAMMADIYAH 1 PEKANBARU - Luh Ayu Laksmi Dewi; Rr. Sri Kartikowati; R M Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the factors that can affect student learning outcomes. This research uses a quantitative descriptive approach. The study population was the XI class students of Accounting at SMK Muhammadiyah 1 Pekanbaru. From a total population of 32 students, and by using a census sampling technique that attracted all students as a sample. The data collection techniques used were documentation techniques to obtain learning outcomes, questionnaire techniques to obtain data about student learning interests and learning facilities at home, and conduct IQ (Intelligence Quotient) test technique to get data about intellectual intelligence. The collected data was then tabulated and analyzed using multiple linear regression with the help of SPSS version 22. The results showed that learning interest, intellectual intelligence and student learning facilities at home had a positive effect on student learning outcomes of class XI Accounting at SMK Muhammadiyah 1 Pekanbaru with the regression equation Y = 50.084 + 0.333X_1 + 0.213X_2 + 0.401X3 and contributed 28.1% to student learning outcomes.Key Words: Factors, Learning Interests, Intellectual Intelligence, Learning Facilities At Home, Learning Outcomes